Effects of Exercise Intensity on Acute Circulating Molecular Responses Poststroke. (March 2020) - Boyne, Pierce; Meyrose, Colleen; Westover, Jennifer; Whitesel, Dustyn; Hatter, Kristal; Reisman, Darcy S.; Carl, Daniel; Khoury, Jane C.; Gerson, Myron; Kissela, Brett; Dunning, Kari
Background . Exercise intensity can influence functional recovery after stroke, but the mechanisms remain poorly understood. Objective . In chronic stroke, an intensity-dependent increase in circulating brain-derived neurotrophic factor (BDNF) was previously found during vigorous exercise. Using the same serum samples, this study tested acute effects of exercise intensity on other circulating molecules related to neuroplasticity, including vascular-endothelial growth factor (VEGF), insulin-like growth factor-1 (IGF1), and cortisol, with some updated analyses involving BDNF. Methods . Using a repeated-measures design, 16 participants with chronic stroke performed 3 exercise protocols in random order: treadmill high-intensity interval training (HIT-treadmill), seated-stepper HIT (HIT-stepper), and treadmill moderate-intensity continuous exercise (MCT-treadmill). Serum molecular changes were compared between protocols. Mediation and effect modification analyses were also performed. Results . VEGF significantly increased during HIT-treadmill, IGF1 increased during both HIT protocols and cortisol nonsignificantly decreased during each protocol. VEGF response was significantly greater for HIT-treadmill versus MCT-treadmill when controlling for baseline. Blood lactate positively mediated the effect of HIT on BDNF and cortisol. Peak treadmill speed positively mediated effects on BDNF and VEGF. Participants with comfortable gait speed ≥0.4 m/s had significantly lower VEGF and higher IGF1 responses, with a lower cortisol response during MCT-treadmill. Conclusions . BDNF and VEGF are promising serum molecules to include in future studies testing intensity-dependent mechanisms of exercise on neurologic recovery. Fast training speed and anaerobic intensity appear to be critical ingredients for eliciting these molecular responses. Serum molecular response differences between gait speed subgroups provide a possible biologic basis for previously observed differences in training responsiveness.